Tai Chi for Stroke Rehabilitation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Lyu, Diyang; Lyu, Xuanxin; Zhang, Yong; Ren, Yi; Yang, Fan; Zhou, Li; Zou, Yihuai; Li, Zongheng (Frontiers in Physiology, 2018)
Tai Chi (TC) has been used wildly around the world for stroke rehabilitation. We conducted a systematic review and meta-analysis to evaluate TC’s efficacy versus conventional rehabilitation therapy in stroke rehabilitation. A total of 21 literatures were included in our study and 14 in quantitative synthesis. Primary outcomes were the modified Barthel Index (BI) for ability of daily living(ADL) , the Fugl-Meyer assessment (FMA) for limb motor function, the Berg Balance scale (BBS) for balance, the Holden scale and To Up-and-Go time (TUGT) for walking ability. Evidence from 9 studies indicated that TC is able to improve independent ADL, whether apply TC with conventional rehabilitation therapy or not. 5 studies reported significant effects of TC plus conventional rehabilitation therapy in increasing the score of FMA of upper limb. The pooling results of BBS revealed significant improvements as well, whether used TC with conventional rehabilitation therapy or not. The results also showed that TC plus conventional rehabilitation therapy could improve walking ability through the Holden scale and TUGT. In conclusion, according to the summary of all outcome data in 21 studies, the current review suggests that TC may have effect on improving ADL, balance, limb motor function and walking ability of stroke survivors with evidences of very low quality, and may improve their sleep quality, mood, mental health and other motor functions. More longer-term, well-designed and high-quality trials are needed to continue developing the quality of evidence in this worthwhile field.